The impact of digital banking on the growth of Micro, Small and Medium Enterprises (MSMEs) in India: A case study - Bharat Kumar Meher; Iqbal Thonse Hawaldar; Latasha Mohapatra; Cristi Spulbăr; Ramona Birau; Cristian Rebegea (Business: Theory and Practice, 2021)
Purpose: The purpose of this paper is to formulate a multiple regression model by considering those factors which are positively affecting the growth of Micro, Small and Medium Enterprises (MSMEs) in India. Methodology: The data used in this study are primary in nature which are collected through questionnaire method. The questionnaire involves the nature and size of business and opinion of the owners and managers of 454 MSMEs in Katihar district, a semi-urban area of Bihar in India, regarding the various favourable factors of digital banking on a Likert scale of 1 to 10. Findings: The findings of the study suggest the various favourable factors of digital banking with significant coefficients i.e. Level of Easiness in accepting payments, Level of Easiness in making payments, Level of Easiness in Managing the expenditure of Business, Level of Time Saving, and Level of Check on Misappropriation or Theft of Cash are contributing towards the growth of MSMEs in India. Research Implications: This research will be helpful to the bank managers and policy makers to encourage the MSMEs of semi-urban areas to use digital banking by stressing on only significant favourable factors and also to take necessary steps so that the MSMEs could reap the full benefits of digital banking. The study could give a new insight regarding the extent of contribution of digital banking towards the growth of MSMEs in rural and semi-urban area.
Keywords: C30; O03; E59; 650; MSMEs; digital banking; e-banking; multiple regression; customer; business